MafhÅ«m al-TaÊ¾lÄ«m fÄ« SÅ«rah LuqmÄn al-Ä€yah 12-19 Ê¿inda TaysÄ«r KarÄ«m al-RahmÄn fÄ« TafsÄ«r KalÄm al-MannÄn liÊ¾Abd al-RahmÄn ibn NÄá¹£ir al-SaÊ¾dÄ« - Alfarouq, Mohammad Hendri; Meinaldi, Lutphi (Atthulab: Islamic Religion Teaching and Learning Journal, 2022)
ØªÙ‡Ø¯Ù Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ ÙˆØµÙ: Ù…ÙÙ‡ÙˆÙ… Ø§Ù„ØªØ±Ø¨ÙˆÙŠÙŠÙ† ÙÙŠ Ø³ÙˆØ±Ø© Ù„Ù‚Ù…Ø§Ù†: Ù¡Ù¢-Ù¡Ù© ÙˆÙ…Ø¯Ù‰ Ø§Ù†Ø¹ÙƒØ§Ø³Ø§ØªÙ‡ Ø¹Ù„Ù‰ Ø§Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©. ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„Ø¨Ø§ØØ«ÙˆÙ† Ø§Ù„Ù…Ù†Ø§Ù‡Ø¬ Ø§Ù„Ù†ÙˆØ¹ÙŠØ© ÙˆØ§Ù„Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„ÙˆØµÙÙŠØ© Ù„Ø£Ù†Ù‡Ø§ ØªØ³ØªÙ†Ø¯ Ø¥Ù„Ù‰ ØªØÙ„ÙŠÙ„ Ø§Ù„ÙˆØ«Ø§Ø¦Ù‚ (Ø§Ù„ÙƒØªØ¨ ÙˆØ§Ù„Ø£ÙˆØ±Ø§Ù‚ Ø§Ù„Ø¹Ù„Ù…ÙŠØ© ÙˆØ§Ù„Ù…Ù„Ø§ØØ¸Ø§Øª ÙˆØºÙŠØ±Ù‡Ø§ Ù…Ù† Ø§Ù„Ù…Ø¹Ø§Ø±Ù). ØªØ¸Ù‡Ø± Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ù¡) ÙŠØ¬Ø¨ Ø£Ù† ÙŠÙƒÙˆÙ† Ù„Ø¯Ù‰ Ø§Ù„ØªØ±Ø¨ÙˆÙŠÙŠÙ† Ù…Ø¹Ø±ÙØ© Ù…Ø¤Ù‡Ù„Ø© Ù„Ù„ØªØ¯Ø±ÙŠØ³ØŒ ÙˆØ£ÙØ¹Ø§Ù„ Ø¬Ø¯ÙŠØ±Ø© Ø¨Ø§Ù„Ø«Ù†Ø§Ø¡ Ø¹Ù„Ù‰ Ø§Ù„ØµØ¹ÙŠØ¯ÙŠÙ† Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠ ÙˆØ§Ù„Ø¯Ø§Ø®Ù„ÙŠØŒ ÙˆÙŠØ³Ø¹ÙˆÙ† Ø¬Ø§Ù‡Ø¯ÙŠÙ† Ù„Ù„ØªÙ†Ø³ÙŠÙ‚ Ø¨ÙŠÙ† Ø§Ù„Ù…Ø¹Ø±ÙØ© ÙˆØ§Ù„Ø¥ØØ³Ø§Ù†ØŒ ÙˆØ£Ù† ÙŠØªÙ…ØªØ¹ÙˆØ§ Ø¨Ø·Ø¨ÙŠØ¹Ø© Ø¹Ø·ÙˆÙØ© ÙˆØµØ§Ø¯Ù‚Ø©. Ù¢) ÙŠØ¬Ø¨ Ø¹Ù„Ù‰ Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„ØªØÙ„ÙŠ Ø¨Ø§Ù„ØµØ¨Ø± ÙÙŠ ØªÙ„Ù‚ÙŠ Ø§Ù„Ø¯Ø±ÙˆØ³. Ù£) ØªÙ‡Ø¯Ù Ø§Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø¥Ù„Ù‰ Ø§Ù„ØªØ£ÙƒÙŠØ¯ Ø¹Ù„Ù‰ Ø§Ù„Ø¹Ø¨ÙˆØ¯ÙŠØ© Ø§Ù„ØØ³Ù†Ø© Ù„Ù„Ù‡ ÙÙŠ Ø§Ù„Ø¥ÙŠÙ…Ø§Ù† ÙˆØ§Ù„Ø¹Ø¨Ø§Ø¯Ø©ØŒ ÙˆØ§Ù…ØªÙ„Ø§Ùƒ Ø§Ù„Ø´Ø®ØµÙŠØ© Ø§Ù„Ø·ÙŠØ¨Ø© ÙˆØ§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ Ø§Ù„ØªÙØ§Ø¹Ù„ Ø¨Ø´ÙƒÙ„ Ø¬ÙŠØ¯ Ù…Ø¹ Ø¥Ø®ÙˆØ§Ù†Ù†Ø§ Ù…Ù† Ø§Ù„Ø¨Ø´Ø±. Ù¤) Ù…ÙˆØ§Ø¯ Ø§Ù„Ø¥ÙƒØ±Ø§Ù‡ Ù‡ÙŠ: Ø§Ù„Ø¹Ù‚ÙŠØ¯Ø©ØŒ ÙˆØ§Ù„Ø¹Ø¨Ø§Ø¯Ø©ØŒ ÙˆØ§Ù„Ø£Ø®Ù„Ø§Ù‚ØŒ ÙˆØ§Ù„Ø¯Ø¹ÙˆØ©. Ù¥) Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙˆØ¬ÙˆØ¯Ø© Ù‡ÙŠ ØªØ±ØºÙŠØ¨ ÙˆØªØ±Ù‡ÙŠØ¨ ÙˆÙ…Ø«Ø§Ù„ÙŠØ©. Ù¦) Ù…Ù† Ø®Ù„Ø§Ù„ ØªÙ†ÙÙŠØ° Ø§Ù„Ù…ÙÙ‡ÙˆÙ… Ø§Ù„ØªØ±Ø¨ÙˆÙŠ Ù„Ù€Ø³ÙˆØ±Ø© Ù„Ù‚Ù…Ø§Ù†: Ø§Ù„Ø¢ÙŠØ§Øª Ù¡Ù¢-Ù¡Ù© Ø§Ù„Ø°ÙŠ ÙŠØ¤ÙƒØ¯ Ø¹Ù„Ù‰ Ø£Ù‡Ù…ÙŠØ© Ø§Ù„ØªÙˆØÙŠØ¯ØŒ Ù…Ù† Ø£Ø¬Ù„ ØªØ¬Ù†Ø¨ ØªÙÙƒÙŠØ± Ø§Ù„ØºØ±Ø¨ÙŠÙŠÙ†. Â This study aims to describe the concept of educators in Surah Luqman: 12-19 and its implications for Islamic education. Researchers use qualitative approaches and descriptive methods based on document analysis (books, scientific papers, notes, and other literacies). The results show that 1) Educators must have qualified knowledge to teach, meritorious deeds both zahir and inner, harmonizing knowledge and charity, and loving and sincere nature. 2) Learners must be patient in receiving lessons. 3) The Islamic education emphasizes the good servitude to Allah, both aqidah and worship, a wonderful personality, and the ability to interact well with fellow humans. 4) Compulsory subjects are aqidah, worship, morals, and da’wah. 5) The methods of education found are targhib wa tarhib and transparency. 6) By carrying out the educational concept of Surah Luqman: 12-19, which emphasizes the importance of tawhid, it will be avoided from western understanding.